Pengembangan Seni Hidangan Alternatif dan Terinspirasi pada Kader Posyandu Balita Sesuai Kandungan Gizi Isi Piringku di Desa Karangsono Kabupaten Jember - Saskia Nadhira Ayudani; Khuliyah Candraning Diyanah; Aditya Sukma Sukma Pawitra; Nur Rahma Febriani; F. Himmatul Aliyah; Ardan Saputra; Na'ilah Putri Az'zahroh; Muhammad Ilham Rofiudin; Triana Pristafania; Akbar Maulana Azhari; Nabila Berlianny Nur Anisa; Ria Lusiandari; Tri Wahyu Suprayogi (GUYUB: Journal of Community Engagement, 2024)
Stunting poses a serious health issue in Indonesia. In 2022, the national prevalence of stunting stood at 22.6%, exceeding the World Health Organization's requirement of below 20%. According to the Indonesian Nutrition Status Survey (SSGI) 2022 by the Ministry of Health, Jember Regency has the highest prevalence of stunted toddlers in East Java, reaching 34.9% or approximately 35,000 toddlers. To address the stunting problem, health efforts are being made through the prevention of stunting diseases with the implementation of the "SEHATI" (Seni Hidangan Alternatif dan Terinspirasi or Alternative or Inspired Food Art) program in Karangsono Village, Bangsalsari Subdistrict, Jember Regency. This program involves community health volunteers managing meals according to the "Isi Piringku" guidelines with appropriate nutritional content for toddlers. The aim of this activity is to raise awareness and knowledge among community health volunteers about the importance of managing balanced and nutritious meals according to the "Isi Piringku" program issued by the Ministry of Health. This study uses a Pre-Experimental Design method with a Pretest-Posttest design model to measure the increase in knowledge of community health volunteers after socialization about the "Isi Piringku" program. The research results show that 90% of volunteers experienced an average knowledge increase of 13.5 after the counseling activities. The "SEHATI" program successfully stimulates children's appetite through unique and appealing foods with balanced nutritional value. The "SEHATI" program is expected to serve as an example for the community in preparing balanced and nutritious meals for children. Through accurate and easily understandable nutrition education, it is hoped that awareness of the importance of healthy and nutritious food intake will increase, ultimately aiding in the prevention of stunting and other nutritional problems in Jember Regency.